DEVELOPMENT AND EVALUATION OF MOBILE APPLICATION PROTOTYPE FOR TREATMENT MONITORING OF SCHIZOPHRENIA PATIENTS - Rahmadini, Fitri
Schizophrenia is a severe chronic mental disorder characterized by disturbances in thought, perception and behaviour. One third of patients with schizophrenia experience nonadherence, which results in patient became tolerant to the drugs given and leading to relapses. Lack of assistance from health workers and lack of knowledge for patients and their families regarding drug information are the reasons for non-adherence with drug consumption. This final project aims to create a mobile-based application prototype to monitor the treatment of schizophrenia patients as a solution to the problem of non-adherence to treatment, namely Schizofriend. The methodology used for application development is Waterfall with the stages of defining requirements, system design, implementation, and system testing. Schizofriend has several features, including medication reminder notifications, drug information, symptoms and side effects monitoring, educational pages, community pages, doctor's control schedule, and profiles which also contain data on the patient's medical and medication history. Prior to the prototype evaluation, patients were interviewed with the MARS-10 questionnaire at one time and found that 95% (n = 20) had adhered to their medication. Evaluation with a single-easequestion showed that all tasks given produce an average score above 5, which means the prototype is easy to operate. However for the system usability scale value at 74,5 which indicates a B grade, acceptable, and categorized in the good range. The analysis showed that Schizofriend is categorized into the passive Net Promoter Score (NPS), which means users will not influence others. Therefore, recommendations are needed for its usability improvements.